Prevalence of Musculoskeletal Sports Injuries of Head, Neck and Upper Limb among Cricket Players: Musculoskeletal Sports Injuries of Head, Neck and Upper - Hussain Umar, Mutahhar; Batool, Sana; Bano Javaid, Hira; Sheraz, Zainab (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
Sports injuries have been reported with growing rate in a quest to identify patterns by which they can be predicted and prevented. Injury investigation in cricket has been started for almost twenty years. Objective: To determine the prevalence of musculoskeletal sports injuries of head, neck and upper limb among cricket players. Methods: It was a Cross-sectional study. Data were taken from 180 selected cricket players from different cricket academies, clubs of Lahore Pakistan. The data were analyzed by SPSS version 21 and with a self-generated questionnaire. Results: This study showed very low prevalence of head and neck injuries which is 5.6 % and very high prevalence of shoulder injuries are seen in this study which is 77.78 %. Elbow injuries are seen 19.4 % while there is a significant association between type of cricketers and shoulder pain. Conclusions: The prevalence of musculoskeletal sports injuries found very high in shoulder joint, then in elbow joint and then in head and neck which has affected their performance. Study also showed a significant correlation between the type of players and shoulder pain